Motivation and Digital Innovation as Determinants of Elementary School Teachers' Performance - Mukhammad Firmansyah; Ahmad Thohirin; M. Furqon Wahyudi (The Future of Education Journal, 2026)
Teacher performance is a crucial factor in determining the success of educational delivery. The increasing demand for teacher professionalism in the era of digital transformation requires teachers to possess strong work motivation and the ability to adopt digital innovations in the teaching and learning process. However, evidence from the field indicates that teachers' levels of motivation and utilization of digital innovation vary considerably, potentially affecting their performance. This study aims to examine the effect of work motivation on teacher performance, the effect of digital innovation on teacher performance, and the simultaneous effect of work motivation and digital innovation on the performance of elementary school teachers in Pasrepan District. This study employed a quantitative approach using an ex post facto research design. The study population consisted of all 70 elementary school teachers in Pasrepan District. A saturated sampling technique was applied, whereby the entire population was included as research respondents. Data were collected using closed-ended questionnaires based on a Likert scale, which had been tested for validity and reliability. The data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS software. The findings indicate that: (1) work motivation has a positive and significant effect on teacher performance (t = 7.599, p < 0.001); (2) digital innovation does not have a significant partial effect on teacher performance (t = 0.270, p = 0.788); and (3) work motivation and digital innovation simultaneously have a positive and significant effect on teacher performance (F = 202.718, p < 0.001). The coefficient of determination (R²) of 0.858 indicates that 85.8% of the variance in teacher performance can be explained by work motivation and digital innovation, while the remaining 14.2% is attributable to other factors not examined in this study. The study concludes that work motivation is the dominant factor influencing the performance of elementary school teachers in Pasrepan District. In contrast, digital innovation does not have a significant partial effect on teacher performance. Therefore, efforts to improve teacher performance should prioritize strengthening teachers' work motivation while simultaneously enhancing their digital competencies and providing adequate technological infrastructure to maximize the benefits of digital innovation for teaching quality and teacher performance.